Adaptability, social support, and psychological wellbeing among university students: A 1-year follow-up study - Holliman, Andrew J.; Waldeck, Daniel; Holliman, David M. (Frontiers in Education, 2022)
The transition to university is a time of great change. A recent literature has shown that adaptability (a personal resource) and social support (a conditional, situational resource) are associated with psychological wellbeing and distress among university students. However, the precise nature of these relations are unclear and there is a paucity of work investigating whether adaptability and social support are predictive of psychological wellbeing and distress over longer periods of time. In the present study, first-year university students (N = 411), were surveyed for their adaptability, social support, and psychological distress, and were then re-assessed for their psychological wellbeing and distress one year later. A series of moderated regression analyses, revealed that adaptability and social support were independent predictors of psychological distress concurrently, and psychological wellbeing one year later. Adaptability, but not social support, was also found to predict psychological distress one year later. No interaction effects were observed. The findings demonstrate the importance of adaptability (and social support to a lesser extent) in predicting psychological wellbeing and distress among university students both at course commencement, but also over the course of their studies one year later.